Estudio doctrinario de la neurocriminología como subdisciplina de la criminología para prevenir los delitos de violencia contra la mujer o miembros del núcleo familiar para el tratamiento de las conductas violentas del agresor - Figueroa Puchaicela, Javier Eduardo (2024)
Neurocriminology, as a subdiscipline of criminology, has emerged as a fascinating field of study that seeks to understand the relationship between neurology and criminal behavior. In particular, it has become a valuable tool for addressing crimes of violence against women and family members, as well as for the treatment of violent behavior in general. The doctrinal approach of neurocriminology allows us to delve into the functioning of the human brain and understand how biological, neuropsychological and social factors influence criminal behavior. Through these studies, we have managed to obtain a better understanding of the neurological bases of violence and, consequently, we have obtained more effective tools to prevent it. Neuroscientific studies have allowed us to identify the brain regions involved in the generation of violent emotions and aggressive behaviors. This information has been essential for the development of therapeutic interventions designed to encourage the inhibition of violent behavior and promote prosocial behaviors. The application of neuroimaging techniques has been especially relevant in the identification and treatment of individuals with violent tendencies. These techniques allow us to detect physiological anomalies in the brain of people that are linked to acts of violence against women or members of the family nucleus. The information obtained through neuroimaging can be used to develop personalized therapeutic treatments, aimed at improving the behavior of these individuals and reducing their risk of recidivism in violence. Neurocriminology has become an essential tool in the prevention and treatment of crimes of violence, especially those directed against women and family members. Through understanding brain functioning and the impact of various factors on criminal behavior, neurocriminology provides us with opportunities to intervene more effectively and promote safer, violence-free societies.